PENGARUH MODEL PICTURE AND PICTURE TERHADAP HASIL BELAJAR SISWA PADA KELAS II SEKOLAH DASAR - Marodha, Khoirum; Supratno, Haris; Siswanto, M. Bambang Edi (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2020)
Learning activities achieved affect the level of understanding of students who impact on learning outcomes, especially in writing skills. The purpose of this study was to find out about the results before and after the use of picture and picture models and the influence of the use of picture and picture models on student learning outcomes in narrative story writing skills in class II SDN Ceweng. Data collection techniques used through observation, tests and documentation. The type of approach used is experimental pre-experimental designs with one-group pretest-posttest design. Data analysis techniques include: (1) normality test and (2) Hypothesis test or T-test. The results of this study can be seen from the results of the calculation in the paired samples test table. If the value of tcount> ttable, then Ho is rejected and H1 is accepted. Based on the above analysis, the result of tcount = 21.777 and df = 35 while ttable = 2.04. Shows that the results of testing the hypothesis Ho are accepted and H1 is rejected. With significance 2 tailed 0,000 <0.05. Meaning strong and there is a significant influence on student learning outcomes.